Studying the Suitability of Roads for Transporting Wind Turbines to Proposed Wind Farm Location - Mahmood , Faleh H.; AbdulAmeer , Sarah Th. (Iraqi Journal of Science, 2022)
The aim of most researchers is to complete full projects for establishing renewable sources stations. The project depend on many variables, which is called criteria, that’s makes the project workable or not. The criterion which studied in this paper is roads suitability for transporting turbines from the loading ports to construction site. One of the important factors which must provide paved roads for transportation and within standard. Southern Um-Qasr port is the best choice to receive wind turbine equipments. The nods down to the construction region will face 0 turns, 2 bridges that crosses over and 23 bridges that passes underneath.